The Cretaceous Normal Superchron: A Mini-Review of Its Discovery, Short Reversal Events, Paleointensity, Paleosecular Variations, Paleoenvironment, Volcanism, and Mechanism - Yoshimura, Yutaka (Frontiers in Earth Science, 2022)
The Cretaceous Normal Superchron (CNS) was first defined in the 1960s to explain the Cretaceous Quiet Zone in marine magnetic anomaly profiles, which includes no or fewer geomagnetic reversals. This ~37 million years period is considered the most unique and extreme geomagnetic feature for the last 160 Myr. Superchrons may be represented when the geodynamo operates at peak efficiency with a unique heat flux condition at the core-mantle boundary, as suggested by geodynamo numerical simulations. Previous studies suggest that CNS was one of the driving forces for the Earth system. During CNS, the geomagnetic intensity may have fluctuated significantly, and the average may have changed with time, and the paleosecular variations had unique features. The warm climate around CNS may have been caused by volcanic activity associated with active mantle convection. Such mantle convection increases heat flux at CMB during CNS, but geodynamo simulations predict small heat flux, which are inconsistent. This discrepancy may be resolved by the growth and collapse of a superplume or by an increase and decrease in the subduction flux.